Farmers’ experience in adoption and usage of ICT solutions for agriculture in the Republic of Macedonia - Vasa, László; Trendov, Nikola (Applied Studies in Agribusiness and Commerce, 2020)
The adoption of new of Information and Communication Technologies (ICTs) in farming activities becoming crucial for developing countries in order to meet the challenges of rapidly growing populations, urbanization and arable agricultural land declination. Because of it, each farmers’ organization or farmer has to concern their agricultural products and services more towards modernized and ICT related routine. The attempt has been made to analyze the reaction of the Macedonian farmers towards ICTs as a source of reliable and timely information about e-banking, online purchasing/selling, marketing, input and output optimization, increased revenue, remote farm management process etc. Semi-structured questionnaire was used for interviewing 132 semi-experienced and experienced farmers that use ICTs as sample for the research. The data were analyzed using appropriate statistics tool like correlation and Rank Based Quotient (RBQ). The findings showed that farmers stressed the cost of ICTs, lack of training, trust level in the government institutions, and lack of ICT infrastructure are thresholds for ICTs adoption and use in agriculture. This research contributes to understand the adoption and use of ICT, identify the constraints associated with ICT use and propose recommendations towards the improvement of ICTs for agriculture in the Republic of Macedonia.